Drugs: From Discovery to Approval - Rick NG (Wiley-Blackwell, 2009)
The new edition of this best-selling book continues to offer a user-friendly, step-by-step introduction to all the key processes involved in bringing a drug to the market, including the performance of pre-clinical studies, the conduct of human clinical trials, regulatory controls, and even the manufacturing processes for pharmaceutical products. Concise and easy to read, the book quickly introduces basic concepts, then moves on to discuss target selection and the drug discovery process for both small and large molecular drugs.This second edition features many key enhancements, including Key Points, Chapter Summary, and Review Questions in each chapter, Answers to Review Questions provided in a book-end appendix, and one or two carefully selected \\\\\\\mini\\\\\\\ case studies in each chapter.Richly illustrated throughout with over ninety figures and tables, this important book also includes helpful listings of current FDA and European guidelines and a special section on regulatory authority and processes in China. It is an indispensable resource for pharmaceutical industry and academic researchers, pharmaceutical managers and executives, healthcare clinicians, policymakers, regulators, and lobbyists with an interest in drug development. It is also an excellent textbook for students in pharmacy, science, and medicine courses.